Analisis Pengukuran Sikap Kepercayaan dan Kepentingan Konsumen Dengan Metode Fishbein Multiatribut Terhadap Produk Gamiku (Edible Bowl) Ekstrak Cangkang Telur - Natasya Khairun Nisa; Septio Catur Nugroho; Adila Hafizhah Batubara; Putri Nadira Gustina; Arifinaya Siti Afifah; Ayutyas Sayekti (CV. ULIL ALBAB CORP, 2025)
The problem of environmental pollution due to plastic waste encourages innovation of environmentally friendly products. One of the innovative products is GaMiku, an edible bowl to replace disposable tableware. The study aims to analyze consumer attitudes towards GaMiku products using the multi-attribute Fishbein model to evaluate the level of importance and trust in product attributes, such as texture, taste, color, packaging, and toppings. Quantitative research was conducted in December 2024 using primary data obtained through a questionnaire survey to 41 respondents. Data analysis involved the calculation of Fishbein scores to understand consumer attitudes towards GaMiku compared to competing products, namely edible cups. The results showed that the most important attributes of GaMiku were texture and taste (1.59), while the color attribute (1.39) had the lowest score. Consumers also rated the trusted attributes on Gamiku, the highest trust score attribute was topping (1.71). Compared to edible cups, GaMiku has a higher total Fishbein score, which is (11.62) compared to (4.61). This shows that consumers prefer GaMiku. Development strategies can be focused on improving color attributes while maintaining excellence in Taste and topping attributes. These results are important for understanding consumer preferences and improving the sustainability of environmentally friendly products.